A subglacial hydrologic drainage hypothesis for silt sorting and deposition during retreat in Pine Island Bay. Issue 80 (23rd December 2019) - Schroeder, Dustin M.; MacKie, Emma J.; Creyts, Timothy T.; Anderson, John B.
Abstract: Late Holocene sediment deposits in Pine Island Bay, West Antarctica, are hypothesized to be linked to intensive meltwater drainage during the retreat of the paleo-Pine Island Ice Stream after the Last Glacial Maximum. The uppermost sediment units show an abrupt transition from ice-proximal debris to a draped silt during the late Holocene, which is interpreted to coincide with rapid deglaciation. The small scale and fine sorting of the upper unit could be attributed to origins in subglacial meltwater; however the thickness and deposition rate for this unit imply punctuated- rather than continuous-deposition. This, combined with the deposit's location seaward of large, bedrock basins, has led to the interpretation of this unit as the result of subglacial lake outbursts in these basins. However, the fine-scale sorting of the silt unit is problematic for this energetic interpretation, which should mobilize and deposit a wider range of sediment sizes. To resolve this discrepancy, we present an alternative mechanism in which the silt was sorted by a distributed subglacial water system, stored in bedrock basins far inland of the grounding line, and subsequently eroded at higher flow speeds during retreat. We demonstrate that this mechanism is physically plausible given the subglacial conditions during the late Holocene. We hypothesize that similar silt units observed elsewhere in Antarctica downstream of bedrock basins could be the result of the same mechanism.